Minimally Invasive Cervical Pedicle Screw Fixation by a Posterolateral Approach for Acute Cervical Injury. Issue 10 (December 2017) - Komatsubara, Tadashi; Tokioka, Takamitsu; Sugimoto, Yoshihisa; Ozaki, Toshifumi
Abstract : Study Design: This is a retrospective case series. Objective: To avoid lateral misplacement of midcervical pedicle screws, T.T., one of our authors, developed a method for minimally invasive cervical pedicle screw (MICEPS) fixation by a posterolateral approach. We reviewed our initial experience with this fixation for trauma cases. Summary of Background Data: Excellent clinical results with cervical screws have been reported for trauma cases. Although cervical pedicle screw fixation can be an essential part of reconstruction in spinal disorders, there is also a risk for injury to the vertebral artery. Methods: This study included 56 consecutive patients who received surgery for cervical fractures. We inserted a total of 203 cervical pedicle screws. Nineteen patients were treated by conventional methods. Thirty-seven patients were treated by MICEPS fixation. According to the MICEPS fixation, 12 patients were treated by unilateral fusion, 25 patients by bilateral fusion. All pedicle screws were inserted using spinal navigation system in the both groups. Results: The average surgical time was 217 minutes with the conventional pedicle screw fixation and 165 minutes with the MICEPS fixation ( P =0.0014). The average intraoperative bleeding was 560 mL in the conventional fixation and 140 mL in the MICEPS fixation ( P <0.0001). Clinically significant screw deviation was significantly lower in the MICEPS fixation group than in the conventional cervical pedicle screw group ( P =0.0039). There was not any deep wound infection in both groups. Conclusions: This intramuscular approach allows for horizontal pedicle screw insertion. This technique is probably useful for reducing intraoperative bleeding. In this study, incidence of screw perforation was significantly lower in the MICEPS fixation group than in the conventional cervical pedicle screw group. In particular, neither of the misplaced screws was laterally deviated in the MICEPS group.